AN INNOVATIVE APPROACH TO THE DIAGNOSIS AND TREATMENT OF WOMEN WITH INFERTILITY DUE TO INTRAUTERINE PATHOLOGIES - Sharipova, Sh.O.; Nazarova, G.G. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. Infertility in women is a serious medical problem that can be caused by many factors, including intrauterine pathologies. The purpose of this study was to develop an innovative approach to the diagnosis and treatment of women with infertility due to intrauterine pathologies. Materials. The study included 60 women: 30 with synechiae in the uterine cavity and 30 with endometrial polyps. The control group included 30 women without pathologies of the uterine cavity. All patients underwent a comprehensive examination, including hysteroscopy, ultrasound, computed tomography, hormonal studies and histological analysis of biopsy material. Results. As a result of the study, an innovative approach to the diagnosis and treatment of women with infertility caused by intrauterine pathologies was developed. The latest technique of computed tomography with the 3D reconstruction of the uterine cavity was used for diagnosis, which made it possible to more accurately determine the nature of the pathology and its localization. For the treatment of synechiae, the method of hysteroscopic resection followed by intrauterine installation of autologous tissue was used, and for the treatment of endometrial polyps, the method of hysteroscopic polypectomy was used. Conclusion. An innovative approach to the diagnosis and treatment of women with infertility caused by intrauterine pathologies is an effective and promising method. The use of the latest diagnostic techniques and an individual approach to treatment allows 2.5 times the achievement of high results in comparison with traditional methods. This approach can be used in clinical practice to improve the effectiveness of infertility treatment in 83.4% of women.